(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2016)
Seasonal investigations of quantitative and qualitative parameters of phytoplankton symbiosis of the Akhpara reservoir was carried out in 2015. It was revealed that more than 45% of recorded algae were indicator species of organic pollution. According to surface waters classifications by trophic and saprobic (eco-sanitary) indices, the water of the Akhpara reservoir was changed from β-oligosaprob level (spring) to β-mesosaprob level (summer, autumn), which indicated that in summer and autumn the level of organic pollution increased. As a result of the study, has been revealed that the number of large single-celled and colonial species in phytoplankton community in 2015 increased compared with previous years.